A GIS-Based Hydrogeological Approach to the Assessment of the Groundwater Circulation in the Ischia Volcanic Island (Italy) - Fabbrocino, Silvia; Bellucci Sessa, Eliana; de Vita, Sandro; Di Vito, Mauro Antonio; Avino, Rosario; Marotta, Enrica (Frontiers in Earth Science, 2022)
Assessing the variations in space and time of groundwater circulation in volcanic islands is of paramount importance in the description of the hydro-geo-thermal system, and implementation of hydrogeological, geochemical, and volcanic monitoring systems. In fact, the reliable reconstruction of the groundwater potentiometric surface in such composite volcanic aquifer systems can enable the identification of the most advantageous strategies for both the sustainable use of groundwater resources and the management of volcanic risk. Geographical Information System (GIS) platforms can support the integration and analysis of many spatial and temporal variables derived from monitoring of active volcanoes, and the elaboration of spatially continuous data. However, open issues still affect the reliability and general applicability of common spatial interpolation methods in the case of groundwater potentiometric surfaces. This is related to the assessment of the main stratigraphic and volcano-tectonic features affecting the hydraulic head changes. With regard to the dynamically very active Ischia Island (Italy), this paper illustrates a GIS-based hydrogeological approach to identify the most accurate interpolation method for mapping the potentiometric surface in complex hydrogeological terrains. The proposed approach has been applied to the existing dataset (1977-2003) stored by the Istituto Nazionale di Geofisica e Vulcanologia. Based on a careful geological and hydrogeological survey, a total of 267 wells, from 5 to 250 m in depth, were processed. The data pre-processing involved four meteorological time series data (1922-1997) and six long records of piezometric water levels (1930-1994). As a result, knowledge of the delineation of rather homogeneous stratigraphic and volcano-tectonic structures at the basin-scale has improved. Thus, new more reliable potentiometric surfaces of the four main geothermal areas closest to the coast were produced, during both dry and wet seasons. The reliability of the processed potentiometric surface was then validated by comparing the spatially continuous data with complementary field data. These findings point towards an optimal interpolation approach for representing the seasonal and areal distribution of main hydrogeological parameters in complex aquifer systems. Finally, insights on variations of hydrological behaviour at an active volcanic area will foster an understanding of possible involvements of fresh and thermal waters in triggering phreatic explosions.